Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/jmi.12995
|View full text |Cite
|
Sign up to set email alerts
|

Protein secondary structure signatures from energy loss spectra recorded in the electron microscope

Abstract: Infrared spectroscopy is a powerful technique for characterising protein structure. It is now possible to record energy losses corresponding to the infrared region in the electron microscope and to avoid damage by positioning the probe in the region adjacent to the structure being studied. Spectra from bacteriorhodopsin, a protein that is predominately a α helix, and OmpF porin, a protein that is mainly β sheet show significant differences over a spectral range from ∼0.1 to 0.25 eV (∼1000 to 1800 cm -1 ). Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Recent studies have suggested a possible damage-free analysis of sensitive specimens in the ULL energy range using the aloof configuration. ,, By focusing the electron probe a few nanometers away from the specimen, the authors recorded an intact signal. This configuration leverages the long-range interactions associated with the phonon excitations to collect a signal without direct impact on the specimen .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have suggested a possible damage-free analysis of sensitive specimens in the ULL energy range using the aloof configuration. ,, By focusing the electron probe a few nanometers away from the specimen, the authors recorded an intact signal. This configuration leverages the long-range interactions associated with the phonon excitations to collect a signal without direct impact on the specimen .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, electron energy-loss spectroscopy (EELS) in the scanning transmission electron microscope (STEM) has emerged as an alternative, more precise technique, as it can access the mid-IR with sub-Ångstrom spatial resolution and as low as 3 meV spectral resolution [16][17][18] . The electron beam can access a number of low-energy excitations including localized phonon modes [19][20][21][22] , molecular vibrations [23][24][25][26] , and the HPhPs [27][28][29] . Moreover, the precise control of the probe enables on-demand excitation of polarization-dependent modes 30 , directly induced localized quasiparticle coupling [31][32][33] , and measurements of polariton dispersions 29,[34][35][36] .…”
Section: Main Textmentioning
confidence: 99%